Ecological Exploitation and Psychological Alienation in Dr. Seuss’ "The Lorax" (2012): A Third-Wave Ecocritical and Ecopsychological Study - Mila Fauziah; Anggawirya Arin Mantara; Margaretha Febriany Narahawarin; Rezky Uspayanti (Litteratura: Jurnal Bahasa dan Sastra, 2026)
This study examines representation of ecopsychology in the relationship between humans and nature as portrayed in film of Dr. Seuss’ The Lorax (2012) adapted from the novel. Employing qualitative descriptive method grounded in third-wave ecocriticism, the research focuses on ecopsychological perspectives to explore emotional and psychological responses to environmental degradation. The data, consisting of dialogues and scenes related to environmental issues, were analyzed through coding. The findings reveal that the commercialization of nature, driven by industrial and business interests, contributes significantly to human alienation from the environment. This alienation generates emotional responses such as awareness, concern, guilt, and regret toward ecological destruction. Moreover, the study demonstrates how denial and disconnection from nature further intensify the exploitation of natural resources and reinforce environmentally destructive behavior. The film portrays ecosystem restoration efforts as an expression of ecological awareness emerging from emotional encounters with environmental loss and damage. Through its narrative, The Lorax not only critiques the destructive consequences of environmental exploitation but also highlights the importance of emotional and psychological connections between humans and nature in developing ecological consciousness. The study concludes that ecopsychology provides an important framework for understanding how emotional engagement with environmental issues can encourage ecological responsibility and strengthen people’s awareness of sustainability and environmental preservation.   Keywords: Ecological Exploitation, Psychological Alienation, Ecocritical, Ecopsychological, Lorax (2012).